Army life in a black regiment - Higginson, Thomas Wentworth, 1823-1911 (Digital Scanning, 2001)
This book - originally a series of essays - was written by a Union colonel from New England, in charge of black troops training off the coast of the Carolinas. It offers a refreshing portrait of life in the Union Army as the narrator captures the raw humor that develops among the men in combat.